Culture Shock Dosen Bahasa Arab Di Masa Pandemic Covid-19 - Maisaroh, Siti; Moh. Ali (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
This study aims to identify the culture shock experienced by lecturers as educators in the realm of higher education during the Covid-19 pandemic. This study used a qualitative approach with analytic descriptive in which data collection used interview techniques. Lecturers as an essential part of lectures are required to remain productive and of high quality, especially in carrying out the obligations of the Tri Dharma of Higher Education. The covid-19 pandemic has forced the world of education in almost all over the world to implement a new system of learning, namely distance learning (virtually). Unfortunately, however, this new system and culture was not fully accepted by university lecturers. Because some feel comfortable and accustomed to adapting to online learning, but others feel culture shock, namely shock, pressure, and cultural shock, because they have never been used to a culture that is considered new. According to this case study research, it was found that junior lecturers experienced mild culture shock, semi-senior lecturers experienced moderate culture shock, while senior lecturers experienced severe culture shock. Keywords: Culture Shock; dosen; pandemi covid-19.